Impact on biocomposites using various types of nanocarbon and polymer - Ain Zaienah, Sueraya; Md Rezaur, Rahman; Khairul Anwar, Mohamad Said; Mohammed Mahbubul, Matin; Mohammed Muzibur, Rahman (Elsevier Ltd., 2024)
The development of environmentally friendly and sustainable materials is improving rapidly in various types of industries worldwide. This includes the development of biocomposites which is defined as a material that is composed of either two or more different types of materials where one of the materials is naturally derived and these materials are combined to produce a new material with enhanced performance compared to its individual constituent materials (Abenojar et al., 2021). The usage of nanotechnology by using natural resources is able to improve the structural and functional properties of the biocomposites (Adamu et al., 2019). Hence, the production of nanocarbon polymer biocomposites are developing rapidly as it combines the superior properties of nanocarbon and natural polymers. Nanocarbon is one of the materials that is able to enhance the mechanical and thermal strength of the polymers and it offers a range of advantages such as energy-efficient, abundant, and high thermal stability (Rizal et al., 2021). To further improve the properties of biocomposites, the usage of natural polymers is also applied which can improve biocompatibility, abundant, less toxic, and biodegradable (Amini et al., 2021).